Asphalt Modifier
The use of a polyester resin with aromatic carboxylic acids and aliphatic alcohols in asphalt modifiers accelerates water resistance development, addressing the issue of moisture penetration and coating deterioration in conventional asphalt pavements.
Patent Information
- Application Number
- JP2020206149
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-11
- Publication Date
- 2025-01-23
- Estimated Expiration
- 2040-12-11
AI Technical Summary
Conventional asphalt pavements exhibit insufficient water resistance, leading to moisture penetration and deterioration of the asphalt coating, and require lengthy curing times, which affect work efficiency.
An asphalt modifier comprising a polyester resin with specific structural units derived from aromatic carboxylic acids and aliphatic alcohols, enhancing the interaction with asphaltene molecules to accelerate water resistance development.
The asphalt modifier facilitates rapid formation of a strong asphalt film on aggregate interfaces, providing quick water resistance development and maintaining coating strength under high-temperature conditions.
Smart Images

Figure 0007620421000001 
Figure 0007620421000002 
Figure 0007620421000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an asphalt modifier, an asphalt composition, an asphalt mixture, a method for producing the same, and a method for paving roads. [Background technology]
[0002] Asphalt pavement, which uses asphalt mixtures, is used for paving roads, parking lots, freight yards, sidewalks, etc., because it is relatively easy to lay. Asphalt pavement has good hardness and durability because the road surface is formed from an asphalt mixture in which aggregate is bound with asphalt.
[0003] Patent Document 1 discloses a bitumen modifier containing as active ingredients a block copolymer containing specific amounts of a polymer block (A) mainly made of a vinyl aromatic hydrocarbon and a polymer block (B) mainly made of a conjugated diene, and an oil-soluble polyester obtained by condensation polymerization of a polyvalent higher carboxylic acid and a polyhydric alcohol, as a bitumen composition having excellent solubility in bitumen, excellent toughness, tenacity, and the like, and also having improved low-temperature properties and storage stability. Patent Document 2 discloses an asphalt composition for road paving that has excellent dry strength, water immersion strength, and petroleum immersion strength, and the asphalt composition contains asphalt, a specific amount of polyester resin, and aggregate, where the polyester resin is a polyester having structural units derived from an alcohol component containing 65 mol % or more of an alkylene oxide adduct of bisphenol A and structural units derived from a carboxylic acid component containing 50 mol % or more of one or more selected from terephthalic acid and isophthalic acid, and has a specific softening point and hydroxyl value. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 08-311299 [Patent Document 2] International Publication No. 2017 / 125421 Summary of the Invention [Problem to be solved by the invention]
[0005] When asphalt pavement is exposed to rainwater or other elements, if the pavement does not have sufficient water resistance, moisture can penetrate and remain between the asphalt and aggregate, peeling off the asphalt coating on the aggregate surface and causing the pavement to turn into gravel. For example, in the conventional techniques disclosed in Patent Documents 1 and 2, a sufficient curing time is required to ensure sufficient water resistance, but a long curing time may result in a decrease in work efficiency. The present invention relates to an asphalt modifier capable of obtaining an asphalt composition and asphalt mixture that exhibit rapid water resistance, an asphalt composition, an asphalt mixture, methods for producing them, and a road paving method. [Means for solving the problem]
[0006] The present invention relates to the following [1] to [6]. [1] An asphalt modifier comprising a polyester resin that is composed of structural units derived from a carboxylic acid component and structural units derived from an alcohol component and that satisfies the following conditions (I) and (II). (I) The carboxylic acid component contains an aromatic carboxylic acid component. (II) The alcohol component contains at least one selected from a branched chain aliphatic alcohol component and a secondary hydroxyl group-containing linear aliphatic alcohol component. [2] An asphalt composition comprising asphalt and the asphalt modifier described in [1] above. [3] A method for producing an asphalt composition, comprising the step of mixing asphalt with the asphalt modifier described in [1] above. [4] An asphalt mixture comprising aggregate and the asphalt composition described in [2] above. [5] A method for producing an asphalt mixture, comprising the step of mixing heated aggregate, asphalt, and the asphalt modifier described in [1] above. [6] A road paving method comprising the step of applying the asphalt mixture described in [4] above to a road to form an asphalt pavement layer. Effect of the Invention
[0007] According to the present invention, it is possible to provide an asphalt modifier, an asphalt composition, an asphalt mixture, methods for producing them, and a road paving method, which are capable of obtaining an asphalt composition and an asphalt mixture that quickly exhibit water resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] [Asphalt modifier] The asphalt modifier of the present invention comprises a polyester resin which comprises structural units derived from a carboxylic acid component and structural units derived from an alcohol component and which satisfies the following conditions (I) and (II). (I) The carboxylic acid component contains an aromatic carboxylic acid component. (II) The alcohol component contains at least one selected from a branched chain aliphatic alcohol component and a secondary hydroxyl group-containing linear aliphatic alcohol component.
[0009] The present inventors have discovered that by incorporating an asphalt modifier consisting of a polyester resin whose carboxylic acid component and alcohol component satisfy specific conditions into an asphalt composition or asphalt mixture, it is possible to obtain an asphalt composition or asphalt mixture that exhibits an excellent rate at which water resistance is developed.
[0010] The reason why the present invention has an advantageous effect is not clear, but is thought to be as follows. In order to increase the coating speed of asphalt on aggregate and hasten the development of water resistance, it is considered important to increase the migration speed of asphaltene, which is an aggregate-adsorbing component in asphalt, to the aggregate interface. In general, polyester resins have a higher affinity with aggregate than asphalt, and migrate faster to the aggregate interface. The polyester resin constituting the asphalt modifier of the present invention contains a structure derived from an aromatic carboxylic acid having an electron-withdrawing aromatic ring, and it is considered that this part effectively interacts with the electron-donating aromatic ring of the asphaltene molecule to form a structure. Furthermore, it is presumed that the inclusion of at least one alcohol component selected from the group consisting of branched-chain aliphatic alcohol components and linear-chain aliphatic alcohol components containing a secondary hydroxyl group strengthens the entanglement between the molecular chains of the polyester resin and the asphaltene molecules, thereby suppressing dissociation of the structures once formed. As a result of the above, it is believed that an asphalt film is formed quickly at the aggregate interface, which accelerates the development of water resistance. In addition, since the strength of the film is maintained even under high temperature and water immersion conditions, it is believed that water resistance will be maintained for a long period of time.
[0011] The definitions of various terms used in this specification are given below. In the polyester resin, a "structural unit derived from a carboxylic acid component" means a structure obtained by removing a hydroxy group from a carboxyl group of a carboxylic acid component, and a "structural unit derived from an alcohol component" means a structure obtained by removing a hydrogen atom from a hydroxy group of an alcohol component. The term "carboxylic acid component" includes not only the carboxylic acid itself, but also anhydrides that decompose during the reaction to generate an acid, and alkyl esters of carboxylic acids (for example, alkyl groups having 1 to 3 carbon atoms). When the carboxylic acid component is an alkyl ester of carboxylic acid, the number of carbon atoms of the alkyl group that is the alcohol residue of the ester is not included in the number of carbon atoms of the carboxylic acid component. A "secondary hydroxy group" refers to a hydroxy group in which the carbon atom to which the hydroxy group is bonded is a secondary carbon atom having two carbon atoms bonded thereto.
[0012] <Polyester resin> The polyester resin is obtained by polycondensation of a carboxylic acid component and an alcohol component. The carboxylic acid component, the alcohol component, and the physical properties of the polyester resin will be described below.
[0013] (Carboxylic acid component) The carboxylic acid component contains at least one aromatic carboxylic acid component from the viewpoint of accelerating the development of water resistance.
[0014] Examples of aromatic carboxylic acids include aromatic monocarboxylic acids, aromatic dicarboxylic acids, and aromatic polyvalent carboxylic acids having a valence of 3 to 6. These aromatic carboxylic acids can be used alone or in combination of two or more. The aromatic carboxylic acid preferably includes an aromatic dicarboxylic acid. Examples of aromatic dicarboxylic acids include terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, anthracenedicarboxylic acid, and phenanthrenedicarboxylic acid. Among these, one or more selected from terephthalic acid and isophthalic acid is preferred, and terephthalic acid is more preferred. Examples of aromatic polycarboxylic acids having a valence of 3 to 6 include trimellitic acid, naphthalenetricarboxylic acid, and pyromellitic acid, and among these, trimellitic acid is preferred. From the viewpoint of hastening the development of water resistance, the content of the aromatic carboxylic acid component is, based on 100 mol% of the carboxylic acid component, preferably 10 mol% or more, more preferably 20 mol% or more, even more preferably 25 mol% or more, even more preferably 30 mol% or more, and even more preferably 40 mol% or more, and 100 mol% or less.
[0015] In one preferred embodiment of the present invention, the carboxylic acid component consists solely of aromatic carboxylic acid components. In another preferred embodiment of the present invention, the carboxylic acid component may contain another carboxylic acid component different from the aromatic carboxylic acid component. Examples of the other carboxylic acid include aliphatic dicarboxylic acids such as oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, adipic acid, sebacic acid, and 1,12-dodecanedioic acid; and aliphatic monocarboxylic acids such as stearic acid, capric acid, lauric acid, myristic acid, palmitic acid, arachidic acid, behenic acid, and lignoceric acid. These other carboxylic acids may be used alone or in combination. In one preferred embodiment of the present invention, the content of the aromatic carboxylic acid component in the carboxylic acid component is preferably 30 mol % or more, more preferably 40 mol % or more, even more preferably 50 mol % or more, even more preferably 60 mol % or more, and even more preferably 80 mol % or more. In one preferred embodiment of the present invention, the content of the aromatic dicarboxylic acid component in the carboxylic acid component is preferably 30 mol % or more, more preferably 40 mol % or more, even more preferably 50 mol % or more, even more preferably 60 mol % or more, and even more preferably 80 mol % or more.
[0016] (Alcohol content) The alcohol component contains at least one selected from a branched chain aliphatic alcohol component and a secondary hydroxyl group-containing linear aliphatic alcohol component, from the viewpoint of hastening the development of water resistance.
[0017] From the viewpoint of hastening the development of water resistance, the branched chain aliphatic alcohol and the secondary hydroxyl group-containing linear aliphatic alcohol preferably have 3 or more carbon atoms and preferably 8.5 or less, more preferably 8.0 or less, more preferably 7 or less, and even more preferably 6 or less. Specific examples of branched chain aliphatic alcohols and secondary hydroxyl group-containing linear aliphatic alcohols include branched chain aliphatic diols or secondary hydroxyl group-containing linear aliphatic diols such as 1,2-propanediol, 1,2-butanediol, 1,3-butanediol, 2,3-butanediol, 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 1,2-pentanediol, 1,3-pentanediol, 1,4-pentanediol, and 3-methyl-1,5-pentanediol. Among them, secondary hydroxyl group-containing linear aliphatic diols are preferred, more preferably 1,2-alkanediols such as 1,2-propanediol and 1,2-butanediol, and even more preferably 1,2-propanediol. These alcohol components may be used alone or in combination. From the viewpoint of hastening the development of water resistance, the total content of the branched chain aliphatic alcohol and secondary hydroxyl group-containing linear aliphatic alcohol components is, in 100 mol % of the alcohol components, preferably 10 mol % or more, more preferably 20 mol % or more, even more preferably 40 mol % or more, even more preferably 50 mol % or more, even more preferably 60 mol % or more, even more preferably 80 mol % or more, even more preferably 90 mol % or more, and is 100 mol % or less.
[0018] In one preferred embodiment of the present invention, the alcohol component consists solely of branched chain aliphatic alcohols and secondary hydroxy group-containing linear aliphatic alcohol components. In another preferred embodiment of the present invention, the alcohol component may contain other alcohol components different from the branched chain aliphatic alcohol and the secondary hydroxyl group-containing linear aliphatic alcohol component. Examples of the other alcohol components include α,ω-aliphatic diol components such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, and 1,12-dodecanediol; aromatic diols such as alkylene oxide adducts of bisphenol A; and trihydric or higher alcohol components such as glycerin, pentaerythritol, and trimethylolpropane. These other alcohol components may be used alone or in combination.
[0019] From the viewpoint of hastening the development of water resistance, the average carbon number of the alcohol component is preferably 3.0 or more and preferably 8.5 or less, preferably 8.0 or less, more preferably 7 or less, and even more preferably 6 or less.
[0020] (molar ratio of carboxylic acid component to alcohol component) From the viewpoint of hastening the development of water resistance, the equivalent ratio of the carboxyl group of the carboxylic acid component to the hydroxyl group of the alcohol component (COOH group / OH group) is preferably 0.5 or more, more preferably 0.6 or more, even more preferably 0.7 or more, and is preferably 1.3 or less, more preferably 1.2 or less, even more preferably 1.1 or less.
[0021] (Physical properties of polyester resin) From the viewpoints of promoting adsorption to aggregate and hastening the development of water resistance, the acid value of the polyester resin is preferably 0.5 mgKOH / g or more, more preferably 1 mgKOH / g or more, even more preferably 1.5 mgKOH / g or more, and is preferably 40 mgKOH / g or less, more preferably 30 mgKOH / g or less, even more preferably 20 mgKOH / g or less. Glass transition temperature (T gFrom the same viewpoints as above, the temperature is preferably 20° C. or higher, more preferably 25° C. or higher, even more preferably 30° C. or higher, and is preferably 100° C. or lower, more preferably 95° C. or lower, even more preferably 90° C. or lower. From the same viewpoints as above, the melt viscosity of the polyester resin at 180°C is preferably 0.1 Pa·s or more, more preferably 0.5 Pa·s or more, even more preferably 1 Pa·s or more, and preferably 50 Pa·s or less, more preferably 40 Pa·s or less, even more preferably 30 Pa·s or less. The acid value, glass transition point and melt viscosity of the polyester resin can be measured by the method described in the Examples. The acid value, glass transition point and melt viscosity can be adjusted by the raw material monomer composition, molecular weight, catalyst amount or reaction conditions.
[0022] (Method of producing polyester resin) The method for producing the polyester resin is not particularly limited, but it can be produced, for example, by polycondensing the above-mentioned alcohol component and carboxylic acid component. The temperature of the polycondensation reaction is not particularly limited, but is preferably 160° C. or higher and 260° C. or lower from the viewpoint of increasing the reactivity and hastening the development of water resistance.
[0023] In the polycondensation reaction, from the viewpoint of reaction rate, a tin(II) compound having no Sn-C bond, such as tin(II) di(2-ethylhexanoate), can be used as an esterification catalyst. From the viewpoint of reaction rate, the amount of the esterification catalyst used is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.2 parts by mass or more, and is preferably 1.5 parts by mass or less, more preferably 1.0 parts by mass or less, and even more preferably 0.6 parts by mass or less, relative to 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. In the polycondensation reaction, in addition to the esterification catalyst, a pyrogallol compound such as gallic acid can be used as a co-catalyst from the viewpoint of reaction rate. The amount of the co-catalyst used is preferably 0.001 parts by mass or more, more preferably 0.005 parts by mass or more, even more preferably 0.01 parts by mass or more, and preferably 0.15 parts by mass or less, more preferably 0.10 parts by mass or less, even more preferably 0.05 parts by mass or less, based on 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component, from the viewpoint of reaction rate. In addition to the catalyst, a polymerization inhibitor such as tertiary butyl catechol can be used in the polycondensation reaction from the viewpoint of reaction rate. The amount of the polymerization inhibitor used is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and preferably 0.5 parts by mass or less, more preferably 0.2 parts by mass or less, based on 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component, from the viewpoint of reaction rate.
[0024] The asphalt modifier of the present invention can be mixed with asphalt, for example, to obtain an asphalt composition. The asphalt composition obtained can be added with aggregate to prepare an asphalt mixture, which can then be used for paving. The asphalt modifier of the present invention can be suitably used as a modifier to be blended into an asphalt mixture containing aggregate.
[0025] [Asphalt composition] The asphalt composition of the present invention contains asphalt and the asphalt modifier. The content of the asphalt modifier is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, even more preferably 1 part by mass or more, and even more preferably 2 parts by mass or more, relative to 100 parts by mass of the asphalt, from the viewpoint of accelerating the development of water resistance, and is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, even more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less, from the viewpoint of workability.
[0026] <Asphalt> As the asphalt, various asphalts can be used. For example, in addition to straight asphalt, which is petroleum asphalt for paving, modified asphalt can be mentioned. Modified asphalts include blown asphalt; polymer modified asphalt modified with polymeric materials such as thermoplastic elastomers and thermoplastic resins, and the like. Straight asphalt is a residual bituminous material obtained by subjecting crude oil to atmospheric distillation equipment, vacuum distillation equipment, and the like. Blown asphalt means asphalt obtained by heating a mixture of straight asphalt and heavy oil, and then blowing air into it to oxidize it. The asphalt is preferably selected from straight asphalt and polymer modified asphalt, and modified asphalt is more preferable from the viewpoint of durability of asphalt pavement, and straight asphalt is more preferable from the viewpoint of versatility.
[0027] (Thermoplastic elastomer) Examples of the thermoplastic elastomer in the polymer modified asphalt include styrene / butadiene block copolymer (hereinafter also referred to as "SB"), styrene / butadiene / styrene block copolymer (hereinafter also referred to as "SBS"), styrene / butadiene random copolymer (hereinafter also referred to as "SBR"), styrene / isoprene block copolymer (hereinafter also referred to as "SI"), styrene / isoprene / styrene block copolymer (hereinafter also referred to as "SIS"), styrene / isoprene random copolymer (hereinafter also referred to as "SIR"), ethylene / vinyl acetate copolymer, ethylene / acrylic acid ester copolymer, styrene / ethylene / butylene / styrene copolymer, styrene / ethylene / propylene / styrene copolymer, polyurethane-based thermoplastic elastomer, polyolefin-based thermoplastic elastomer, isobutylene / isoprene copolymer, polyisoprene, polychloroprene, synthetic rubber other than the above, and at least one selected from natural rubber.
[0028] Among these, from the viewpoint of durability of asphalt pavement, the thermoplastic elastomer is preferably at least one selected from SB, SBS, SBR, SI, SIS, SIR, and ethylene / acrylic acid ester copolymers, more preferably at least one selected from SB, SBS, SBR, SI, SIS, and SIR, and even more preferably at least one selected from SBR and SBS. From the viewpoint of the durability of the asphalt pavement, the content of the thermoplastic elastomer in the polymer modified asphalt is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, even more preferably 1 mass% or more, and preferably 30 mass% or less, more preferably 15 mass% or less, even more preferably 5 mass% or less.
[0029] From the viewpoint of exerting asphalt performance, the asphalt content in the asphalt composition is preferably 60 mass% or more, more preferably 65 mass% or more, and even more preferably 70 mass% or more, and from the viewpoint of storage stability, it is preferably 99 mass% or less, more preferably 98 mass% or less, and even more preferably 97 mass% or less.
[0030] [Method of producing asphalt composition] The method for producing an asphalt composition of the present invention includes a step of mixing asphalt with the asphalt modifier. That is, the asphalt composition of the present invention is an asphalt composition obtained by blending asphalt and the asphalt modifier. The asphalt composition can be obtained by heating and melting the asphalt, adding the asphalt modifier, and stirring and mixing the components in a commonly used mixer until they are uniformly dispersed. Commonly used mixers include homomixers, dissolvers, paddle mixers, ribbon mixers, screw mixers, planetary mixers, vacuum countercurrent mixers, roll mills, twin-screw extruders, etc.
[0031] The mixing temperature of the asphalt and the asphalt modifier is preferably 130°C or higher, more preferably 150°C or higher, even more preferably 170°C or higher, from the viewpoint of uniformly dispersing the polyester resin that constitutes the asphalt modifier in the asphalt, and is preferably 230°C or lower, even more preferably 210°C or lower, more preferably 200°C or lower. Furthermore, the mixing time between the asphalt and the asphalt modifier is preferably 30 seconds or more, more preferably 1 minute or more, and even more preferably 2 minutes or more, from the viewpoint of efficiently dispersing the polyester resin that constitutes the asphalt modifier uniformly in the asphalt, and is preferably 2 hours or less, more preferably 1 hour or less, and even more preferably 30 minutes or less. The asphalt composition of the present invention is a binder composition, and can be used for paving after, for example, adding aggregate to the asphalt composition to form an asphalt mixture. That is, the asphalt composition of the present invention is suitable for paving, and is particularly suitable for road paving.
[0032] [Asphalt mixture] The asphalt mixture of the present invention contains aggregate and the asphalt composition described above. That is, the asphalt mixture contains at least aggregate, asphalt, and the asphalt modifier described above.
[0033] The content of the asphalt modifier in the asphalt mixture is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, even more preferably 0.10 mass% or more, even more preferably 0.15 mass% or more, and preferably 4 mass% or less, more preferably 3 mass% or less, even more preferably 2 mass% or less, even more preferably 1 mass% or less. The asphalt content in the asphalt mixture is preferably 2.5 mass% or more, more preferably 3 mass% or more, even more preferably 3.5 mass% or more, even more preferably 4 mass% or more, and preferably 10 mass% or less, more preferably 9 mass% or less, even more preferably 8 mass% or less, even more preferably 7 mass% or less.
[0034] <Aggregate> The aggregate may be any material selected from crushed stone, boulders, gravel, sand, recycled aggregate, ceramics, etc. In addition, the aggregate may be either coarse aggregate with a particle size of 2.36 mm or more, or fine aggregate with a particle size of less than 2.36 mm. Examples of coarse aggregate include crushed stone with a particle size range of 2.36 mm or more and less than 4.75 mm, crushed stone with a particle size range of 4.75 mm or more and less than 12.5 mm, crushed stone with a particle size range of 12.5 mm or more and less than 19 mm, and crushed stone with a particle size range of 19 mm or more and less than 31.5 mm. The fine aggregate is preferably one having a particle size of 0.075 mm or more and less than 2.36 mm. Examples of fine aggregate include river sand, dune sand, mountain sand, sea sand, crushed sand, fine sand, screenings, crushed stone dust, silica sand, artificial sand, glass cullet, foundry sand, and recycled crushed aggregate sand. The above particle size is the value specified in JIS A5001:2008. Among these, a combination of coarse aggregate and fine aggregate is preferable.
[0035] The fine aggregate may contain a filler having a particle size of less than 0.075 mm. Examples of the filler include sand, fly ash, calcium carbonate such as limestone powder, and slaked lime. Among these, calcium carbonate is preferred from the viewpoint of improving the strength of the asphalt pavement. From the viewpoint of improving the strength of the asphalt pavement, the average particle size of the filler is preferably 0.001 mm or more, and preferably 0.05 mm or less, more preferably 0.03 mm or less, and further preferably 0.02 mm or less. Here, the average particle size means the average particle size at 50% cumulative volume.
[0036] From the viewpoint of the durability of the asphalt pavement, the mass ratio of coarse aggregate to fine aggregate is preferably 10 / 90 or more, more preferably 15 / 85 or more, even more preferably 20 / 80 or more, and is preferably 90 / 10 or less, more preferably 80 / 20 or less, even more preferably 70 / 30 or less.
[0037] The aggregate content in the asphalt mixture is preferably 90% by mass or more, preferably 92% by mass or more, preferably 93% by mass or more, and preferably 98% by mass or less, preferably 97% by mass or less, preferably 96% by mass or less.
[0038] Suitable examples of blending the asphalt mixture include the following (1) to (3). (1) Fine-grained asphalt containing 30% by volume or more but less than 45% by volume of coarse aggregate, 30% by volume or more but less than 50% by volume of fine aggregate, and 5% by volume or more but less than 10% by volume of an asphalt composition. (2) An example of an asphalt mixture is a dense-graded asphalt mixture containing, for example, 45% to less than 70% by volume of coarse aggregate, 20% to 45% by volume of fine aggregate, and 3% to 10% by volume of an asphalt composition. (3) Porous asphalt containing 70% by volume or more and 80% by volume or less of coarse aggregate, 10% by volume or more and 20% by volume or less of fine aggregate, and 3% by volume or more and 10% by volume or less of an asphalt composition. The mixing ratio of asphalt in conventional asphalt mixtures containing aggregate and asphalt is usually determined according to the optimal amount of asphalt obtained from the "Mix Design of Asphalt Composition" described in the "Guidelines for Pavement Design and Construction" issued by the Japan Road Association, a public interest incorporated association. In the present invention, the above-mentioned optimum amount of asphalt corresponds to the total amount of asphalt and asphalt modifier. However, it is not necessary to be limited to the method described in the "Guidelines for Pavement Design and Construction" and it may be determined by other methods.
[0039] <Additives> In addition to the aggregate, asphalt, and asphalt modifier described above, the asphalt mixture of the present invention may contain, as necessary, various additives that have been conventionally used in asphalt mixtures, such as film-forming agents, thickening stabilizers, and emulsifiers. Specific examples of such materials include fillers and reinforcing agents such as mineral powder and glass fiber, mineral aggregates, pigments such as red iron oxide and titanium dioxide, waxes such as paraffin wax, microcrystalline wax and low molecular weight polyethylene wax, foaming agents such as azodicarbonamide, polyolefin-based or low molecular weight vinyl aromatic thermoplastic resins such as atactic polypropylene and ethylene-ethyl acrylate copolymers, natural rubber, polyisoprene rubber, polybutadiene rubber, styrene-butadiene rubber, ethylene-propylene rubber, chloroprene rubber, acrylic rubber, isoprene-isobutylene rubber, polypentenamer rubber, styrene-butadiene block copolymers, styrene-isoprene block copolymers, hydrogenated styrene-butadiene block copolymers, and hydrogenated styrene-isoprene block copolymers. The total amount of these additives is preferably 50% by mass or less, more preferably 25% by mass or less, and even more preferably 5% by mass or less, based on the entire asphalt mixture.
[0040] [Asphalt mixture manufacturing method] The method for producing an asphalt mixture of the present invention includes a step of mixing asphalt, heated aggregate, and an asphalt modifier simultaneously or in any order. That is, the asphalt mixture of the present invention is an asphalt mixture obtained by blending asphalt, aggregate, and the above-mentioned asphalt modifier. Specific methods for producing asphalt mixtures include conventional methods for producing asphalt mixtures called the plant mix method, the premix method, etc. In both methods, asphalt and an asphalt modifier are added to heated aggregate. The above mixing step is preferably any one of the following steps (i) to (iii). (i) A method in which heated aggregate and asphalt are mixed to obtain a mixture, and then the mixture is mixed with an asphalt modifier. (ii) A method in which asphalt and asphalt modifier are added and mixed simultaneously with heated aggregate. (iii) A method in which a premixed mixture of asphalt and asphalt modifier is added to and mixed with the heated aggregate. Among these, from the viewpoint of durability of asphalt pavement, method (i) is preferred.
[0041] In the methods (i) to (iii), the temperature of the heated aggregate is preferably 130°C or higher, more preferably 150°C or higher, and even more preferably 170°C or higher from the viewpoint of durability of the asphalt pavement, and is preferably 230°C or lower, more preferably 210°C or lower, and even more preferably 200°C or lower from the viewpoint of preventing thermal deterioration of the asphalt.
[0042] The mixing temperature of the aggregate with the asphalt and / or asphalt modifier is preferably 130°C or higher, more preferably 150°C or higher, and even more preferably 170°C or higher from the viewpoint of the durability of the asphalt pavement, and is preferably 230°C or lower, more preferably 210°C or lower, and even more preferably 200°C or lower from the viewpoint of preventing thermal deterioration of the asphalt. The mixing time of the aggregate with the asphalt and / or asphalt modifier is not particularly limited, but is preferably 30 seconds or more, more preferably 1 minute or more, even more preferably 2 minutes or more, and is preferably 2 hours or less, more preferably 1 hour or less, even more preferably 30 minutes or less.
[0043] From the viewpoint of durability of the asphalt pavement, the method for producing an asphalt mixture preferably includes a step of mixing asphalt, aggregate, and asphalt modifier, and then holding the resulting asphalt mixture at the above-mentioned mixing temperature or at a temperature equal to or higher than the mixing temperature. In the step of maintaining the asphalt mixture, the mixture may be further mixed. The retention time is preferably 0.25 hours or more, more preferably 0.5 hours or more, and even more preferably 1 hour or more, and the upper limit of the time is not particularly limited, but is, for example, about 5 hours. The retention time for exerting the effects of the present invention may be 3 hours or less, preferably 1 hour or less, and more preferably 0.5 hours or less.
[0044] [Road paving method] The asphalt mixture of the present invention is suitable for road paving, and as described above, an asphalt mixture obtained by adding aggregate to an asphalt composition is used for road paving. The road paving method includes a step of applying the asphalt mixture to a road to form an asphalt pavement layer. Specifically, the road paving method includes a step (step 1) of obtaining an asphalt mixture by mixing asphalt, the asphalt modifier, and aggregate, and a step (step 2) of applying the asphalt mixture obtained in step 1 to a road to form an asphalt pavement layer. The asphalt pavement layer is preferably a base layer or a surface layer.
[0045] The asphalt mixture may be compacted and applied in a similar manner using a known construction machine. The compaction temperature when used as a heated asphalt mixture is preferably 100°C or higher, more preferably 120°C or higher, and even more preferably 130°C or higher, from the viewpoint of the durability of the asphalt pavement, and is preferably 200°C or lower, and more preferably 180°C or lower. EXAMPLES
[0046] Various physical properties were measured and evaluated by the following methods. In the following examples and comparative examples, parts and percentages are by weight unless otherwise specified.
[0047] [Acid value of polyester resin] The acid value of the polyester resin was measured based on the method of JIS K0070: 1992. However, the measurement solvent was changed from the mixed solvent of ethanol and ether specified in JIS K0070: 1992 to a mixed solvent of acetone and toluene (acetone:toluene = 1:1 (volume ratio)).
[0048] [Glass transition temperature of resin (T g )] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan Co., Ltd.), 0.01 to 0.02 g of the sample was weighed into an aluminum pan, heated to 200°C, and cooled to 0°C at a rate of 10°C / min. Measurements were then performed while heating to 150°C at a rate of 10°C / min. The glass transition point was determined as the temperature at the intersection of an extension of the baseline below the maximum endothermic peak temperature and a tangent line showing the maximum slope from the rising part of the peak to the top of the peak.
[0049] [Melt viscosity of polyester resin] The viscosity of the polyester resin was measured using a rotational viscometer DV1 Viscometer (manufactured by Brookfield). The sample was set in a viscometer thermocell (manufactured by Brookfield) and heated to 180°C, after which the measurement was started. The viscosity value when the measured value stabilized after 25 to 35 minutes had elapsed from the start of the measurement was taken as the melt viscosity.
[0050] Manufacturing Examples 1 to 3, 5 to 10 (Polyester Resins A1 to A3, A5 to A10) The raw material monomers shown in Tables 1 and 2 were placed in a 10L four-neck flask equipped with a thermometer, a stainless steel stirring rod, a dehydration tube, a nitrogen inlet tube, and a thermocouple, and the mixture was kept at 140°C for 6 hours under a nitrogen atmosphere, and then heated to 200°C over 6 hours. Then, tin(II) di(2-ethylhexanoate) and gallic acid were added in the amounts shown in the tables under a nitrogen atmosphere, and the mixture was reacted at 200°C for 1 hour, and then reacted under reduced pressure of 8.3 kPa for 1 hour to obtain polyester resins A1 to A3 and A5 to A10. The results are shown in Tables 1 and 2.
[0051] Manufacturing Examples 4 and 11 (Polyester Resin A4 and A11) Raw material monomers other than adipic acid shown in Tables 1 and 2 were placed in a 10L four-neck flask equipped with a thermometer, a stainless steel stirring rod, a dehydration tube, a nitrogen introduction tube, and a thermocouple, and the amounts of di(2-ethylhexanoate)tin(II) and gallic acid shown in the tables were added under a nitrogen atmosphere, and the temperature was raised to 180°C. After keeping at 180°C for 1 hour, the temperature was raised from 180°C to 210°C at a rate of 10°C / hour, and then a condensation polymerization reaction was carried out at 210°C for 7 hours, and further a reaction was carried out for 1 hour under reduced pressure conditions of 210°C and 8.3kPa. Next, adipic acid was added, and the reaction was carried out at 210°C and 10kPa until the acid value shown in Tables 1 and 2 was reached, to obtain polyester resins A4 and A11. The results are shown in Tables 1 and 2.
[0052] [Table 1]
[0053] [Table 2]
[0054] Production Example 12 (Polyester Resin B1) The raw material monomers shown in Table 3 were placed in a 5L four-neck flask equipped with a thermometer, a stainless steel stirring rod, a dehydration tube, a nitrogen inlet tube, and a thermocouple, and monobutyltin oxide was added in the amount shown in the table under a nitrogen atmosphere, and the temperature was raised to 100°C. Next, the temperature was raised from 100°C to 260°C over 6 hours while removing water produced during the reaction and unreacted diol. The reaction was then continued for 10 hours while dehydrating at 260°C, to obtain polyester resin B2. The results are shown in Table 3.
[0055] Production Example 13 (Polyester Resin B2) The raw material monomers shown in Table 3 were placed in a 10 L four-neck flask equipped with a thermometer, a stainless steel stirring rod, a dehydration tube, a nitrogen inlet tube, and a thermocouple, and kept at 140°C for 6 hours under a nitrogen atmosphere, and then heated to 230°C over 6 hours. Then, tin(II) 2-ethylhexanoate and gallic acid in the amounts shown in the table were added and reacted at 230°C for 1 hour, and then at 8.3 kPa for 1 hour to obtain polyester resin B2. The results are shown in Table 3. The melting point of the polyester resin B2 was measured.
[0056] [Table 3]
[0057] The abbreviations and details of the carboxylic acid components used are as follows: Dimer acid: Haridimer 270S (Harima Chemicals Co., Ltd.) In addition, in Tables 1 to 3, the "molar ratio" is the molar ratio relative to the total of the alcohol components, 100 mol %.
[0058] In the following examples, asphalt was used was asphalt (straight asphalt) manufactured by Associated Asphalt and having a PG grade of 64-22. The aggregate used was manufactured by Blythe Construction Co., Ltd. The aggregate (3000 g) contained 750 g of gravel (coarse aggregate), 1950 g of screenings (fine aggregate), and 300 g of mountain sand (fine aggregate). The mass percentage of each component was as follows: <Aggregate composition> [gravel] Sieve size 9.50mm: 90.4% by mass Sieve size 8.00mm: 73.3% by mass Sieve size 4.75mm: 24.8% by mass Sieve size 2.80mm: 3.9% by mass Sieve size 1.00mm: 1.2% by mass Sieve size 0.50mm: 0.8% by mass [Screenings] Sieve size 9.50mm: 100.0% by mass Sieve size 8.00mm: 99.9% by mass Sieve size 4.75mm: 98.2% by mass Sieve size 2.80mm: 77.4% by mass Sieve size 1.00mm: 36.8% by mass Sieve size 0.50mm: 22.1% by mass [Mountain sand] Sieve size 9.50mm: 100.0% by mass Sieve size 8.00mm: 100.0% by mass Sieve size 4.75mm: 98.0% by mass Sieve size 2.80mm: 94.2% by mass Sieve size 1.00mm: 70.6% by mass Sieve size 0.50mm: 33.6% by mass
[0059] Example 1-1 (Preparation of Asphalt Composition AS-1) Glass marbles (diameter 17 mm) manufactured by Artec Co., Ltd. were used as aggregate. 200 g of marbles were weighed in a 500 mL stainless steel beaker and heated to 180 ° C., and 10.0 g of asphalt (Associated Asphalt, straight asphalt PG64-22) heated to 180 ° C. was added to it and mixed with a metal spatula for 1 minute. 0.5 g of polyester resin A1 was further added and mixed for 1 minute. The obtained asphalt composition AS-1 was divided into 12 samples of about 15 g each, and all of the samples were placed in a constant temperature bath at 180 ° C. After addition, one divided sample was removed from the thermostatic chamber at each of the following times: 15, 30, 40, 50, 60, 70, 80, 90, 120, 150, 180, and 240 minutes, and cooled to room temperature. Each sample was then spread on a mesh with 1 mm openings and immersed in 85°C water for 3 minutes. After immersion, the percentage of the area of the asphalt coating that had not peeled off from the marble surface was measured, and this was taken as the coverage rate. Measurement method: Using a vernier caliper, measure the area E of the part where the asphalt coating has peeled off and the marble surface is exposed. n(n = 1, 2, ...; n is an integer representing the total number of areas where the asphalt coating has peeled off and the marble surface is exposed.) was calculated for each. In addition, the total surface area value S of the marble was calculated from the diameter of the marble. The coverage rate was calculated using the following formula.
[0060]
number
[0061] Based on the measured coverage, the minimum curing time (min) required for a coverage rate of >99% was determined as an index for evaluating the film formation rate. The results are shown in Table 4.
[0062] Examples 1-2 to 1-11, Comparative Examples 1-1 to 1-3 Asphalt compositions AS-2 to AS-11 and AS-C1 to AS-C3 were prepared in the same manner as in Example 1-1, except that the formulation was changed to that shown in Table 4. The minimum curing time (min) required for a coverage rate of >99% was determined, and the results are shown in Table 4.
[0063] [Table 4]
[0064] Example 2-1 (Preparation of asphalt specimen M-1) [Preparation of specimens for water resistance evaluation test] 1300g of aggregate preheated to 180°C was weighed into a mortar mixer and mixed at 180°C for 30 seconds. Then, 71g of asphalt (Associated Asphalt, straight asphalt PG64-22) was added and mixed for 1 minute. After that, 3.55g of polyester resin A1 was added and mixed for another 1 minute. After storing the resulting asphalt mixture at 180°C for 15 minutes, about 1200g of the mixture was filled into a formwork, and molded by tamping on both sides 50 times on one side using an automatic asphalt tamping device (NA-507) manufactured by Nakajima Gihan Co., Ltd., and then allowed to cool to room temperature for 15 hours to obtain asphalt specimen M-1.
[0065] Examples 2-2 to 2-11, Comparative Examples 2-1 to 2-3 Except for changing the blend ratio as shown in Table 2, asphalt specimens M-2 to M-11 and M-C1 to M-C3 were prepared in the same manner as in Example 2-1.
[0066] [Water resistance evaluation: Marshall stability test] Using the asphalt specimens prepared by the above method, the standard Marshall stability (kN) and water immersion Marshall stability (kN) were calculated by Marshall stability tests. The Marshall stability test was carried out according to the procedure described in the Pavement Survey and Testing Method Handbook B001 "Marshall Stability Test Method," and the evaluation equipment used was Nakajima Gihan's "Marshall Cracking Test Loading Apparatus (Model No. NA-506)." Note that the standard Marshall stability is the stability when the test piece is immersed in 60°C water for 30 minutes, and the water-immersed Marshall stability is the stability when the test piece is immersed in 60°C water for 48 hours. From the measured standard Marshall stability and water immersion Marshall stability, the residual stability (%) was calculated using the following formula (A) to evaluate water resistance. Residual stability (%) = [Water immersion Marshall stability / Standard Marshall stability] x 100 (A) The closer the residual stability value is to 100%, the better the water resistance of the asphalt mixture. The results are shown in Table 5.
[0067] [Table 5]
[0068] From Table 4, it can be seen that the asphalt modifier of the present invention makes it possible to obtain an asphalt composition that can achieve a coverage rate of >99% in a short curing time in an evaluation test using glass marbles as aggregate. Furthermore, Table 5 shows that even when asphalt specimens are prepared with a short curing time, it is possible to obtain an asphalt mixture that exhibits excellent water resistance and quickly develops water resistance.
Claims
1. An asphalt modifier comprising a polyester resin which comprises a structural unit derived from a carboxylic acid component and a structural unit derived from an alcohol component and which satisfies the following conditions (I) and (II). (I) The carboxylic acid component contains at least one aromatic carboxylic acid component selected from an aromatic dicarboxylic acid and an aromatic polycarboxylic acid having a valence of 3 to 6 in an amount of 80 mol % or more in the carboxylic acid component. (II) The alcohol component contains at least one selected from a branched chain aliphatic diol component and a secondary hydroxyl group-containing linear aliphatic diol component in an amount of 60 mol % or more in the alcohol component.
2. The asphalt modifier described in claim 1, which is incorporated into an asphalt composition containing asphalt, or an asphalt mixture containing asphalt and aggregate, and used to improve water resistance.
3. 3. The asphalt modifier according to claim 1 or 2, wherein the aromatic carboxylic acid component comprises an aromatic dicarboxylic acid.
4. The asphalt modifier according to any one of claims 1 to 3, wherein the average carbon number of the alcohol component is 3.0 or more and 8.5 or less.
5. The asphalt modifier according to any one of claims 1 to 4, wherein the alcohol component comprises 1,2-propanediol.
6. The asphalt modifier according to any one of claims 1 to 5, wherein the polyester resin has a melt viscosity at 180 ° C. of 0.1 Pa · s or more and 50 Pa · s or less.
7. An asphalt composition comprising asphalt and the asphalt modifier according to any one of claims 1 to 6.
8. A method for producing an asphalt composition, comprising a step of mixing asphalt with the asphalt modifier according to any one of claims 1 to 6.
9. An asphalt mixture comprising aggregate and the asphalt composition of claim 7.
10. A method for producing an asphalt mixture, comprising a step of mixing heated aggregate, asphalt, and the asphalt modifier according to any one of claims 1 to 6.
11. A road paving method, comprising a step of applying the asphalt mixture according to claim 9 to a road to form an asphalt pavement layer.
Citation Information
Patent Citations
Anti-asphalt paint, composite polyester resin and preparation methods thereof
CN101921520A
Micro-nano filler made from PET (polyethylene terephthalate) material, and preparation method and application thereof
CN109824938A
Bitumen modifier and bitumen composition
JP1996311299A
Method for producing plastic composition for pavement material
JP2006096799A
Asphalt composition for road pavement
WO2017125421A1